2009
DOI: 10.1007/s10646-009-0415-1
|View full text |Cite
|
Sign up to set email alerts
|

Avian liver organochlorine and PCB from South coast of the Caspian Sea, Iran

Abstract: Liver samples (n = 43) of 9 avian species representing the families Phalacrocoracidae, Podicipedidae, Laridae, and Anatidae, were collected from the Iranian coast of the Caspian Sea. Samples were analyzed for organochlorine pesticides (OCPs), such as dichlorodiphenyltrichloroethane (DDT) and its metabolites, hexachlorobenzene (HCB), hexachlorocyclohexane isomers (HCHs), and seven PCB congeners. p,p'-DDE was predominantly found in all species, at concentrations ranging from the limit of quantification (LOQ) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Research conducted in various regions of the world indicates that PCBs are still present in the marine environment (Falkowska et al 2016 ; Huber et al 2015 ; Robinson et al 2015 ; Roscales et al 2016 ; Wolschke et al 2015 ; Zheng et al 2018 ) (Table 5 ). Wilson et al ( 2010 ) and Rajaei et al ( 2010 ) reported that the liver of birds from South coast of British Columbia, Canada and Caspian Sea contained 10–30 ng PCBs/g ww. For comparison, the concentration of PCBs in eggs of Common eider from Røst, Norway was 2-fold higher: 76.9 ng/g ww (Huber et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Research conducted in various regions of the world indicates that PCBs are still present in the marine environment (Falkowska et al 2016 ; Huber et al 2015 ; Robinson et al 2015 ; Roscales et al 2016 ; Wolschke et al 2015 ; Zheng et al 2018 ) (Table 5 ). Wilson et al ( 2010 ) and Rajaei et al ( 2010 ) reported that the liver of birds from South coast of British Columbia, Canada and Caspian Sea contained 10–30 ng PCBs/g ww. For comparison, the concentration of PCBs in eggs of Common eider from Røst, Norway was 2-fold higher: 76.9 ng/g ww (Huber et al 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The amounts of wastewater discharged into the WWTP were about 8,000 m 3 per day. 19), respectively. The working standard solutions were prepared by diluting appropriate volumes of the standard PCB mixture with HPLC-grade nhexane.…”
Section: Sampling Sitesmentioning
confidence: 98%
“…In this zone, the wastewater discharged by pigment and dyeing chemical industries accounts for about 70% of the total industrial wastewater. Data provided by US EPA and other workers indicate that PCBs have been found in various color dyestuff and pigments [3,[17][18][19]. Rodenburg and colleagues knew PCB-11 was linked to the manufacture of diarylide yellow pigments [3].…”
Section: Source Analysis Of Pcbs From Dyeing Chemical Industrymentioning
confidence: 99%
See 1 more Smart Citation